APLIKASI MAQASID ASY-SYARI‘AH PADA SISTEM KEUANGAN SYARIAH - Zaki, Muhammad; Cahya, Bayu Tri (BISNIS, 2015)
Maqas'id  asy-shari’ah  is relevant koredor as a basis for the development of the system, practice, and sharia banking products. The order of maqas'id asy-shari’ah is the way the light for the journey of sharia banking in answer the question dynamic based on the common good and welfare. The concept of Islamic economy is a prerequisite that must be developed further, not only in the conceptual overtones teapi also in practical overtones, especially in the practice of sharia banking. Islam has been providing textual sources that adequate to provide limitations prioritising man, but it is not enough if not balanced with social inferensi.  The theory maqas'id  asy-shari’ah  in the study of the Islamic economy is a step forward in the development of Islamic economic model that most ideal. This is because the maqas'id asyshari’ah can be used as the tool to help resolve the argument in specify a law in order to achieve the goal of shortening the law.